Effectiveness of Virtual Reality Distraction in Reducing Pain, Fear, and Anxiety Among Children Undergoing Invasive Procedures: A Systematic Review - farid_talango; Cahyaningtyas, Anindhita Yudha (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2025)
Invasive medical procedures such as venipuncture often cause pain, fear, and anxiety in children. Virtual Reality (VR) is an immersive technology that is increasingly used as a non-pharmacological distraction tool to reduce such discomfort. This study is a systematic review conducted following the PRISMA guidelines. Literature searches were performed across Google Scholar, ProQuest, PubMed, ScienceDirect, and SpringerLink using the keywords: